2010
DOI: 10.1099/vir.0.023838-0
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-specific anti-prion antibodies upregulate apolipoprotein E and disrupt membrane cholesterol homeostasis

Abstract: The mechanisms of neuronal degeneration induced by the transformation of normal cellular prion protein (PrP C ) into disease-associated PrP Sc are not fully understood. Previous reports have demonstrated that cross-linking cellular prion protein by anti-PrP C antibodies can promote neuronal apoptosis. In this report, we now show that treatment of neuronal cells with anti-prion antibodies leads to sequestration of free cholesterol in cell membranes, significant overexpression of apolipoprotein E, and to cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Furthermore, inhibition of mGluRs, known to regulate histamine (34), abolished the anti-PrP antibody toxic effects (28). Taken together and in addition to the allergenic-related proteins associated with ICSM35 treatment reported by Tayebi and colleagues (21), this provides sufficient evidence to investigate the allergenic pathways potentially induced by treatment with anti-PrP antibodies which we refer to as "IgG-Mediated Neuronal Hypersensitivity". To that end, we treated mouse primary neurons (MPN), mouse neuroblastoma (N2a) and microglia (N11) cell lines with anti-PrP antibodies then assessed the neuronal allergenic proteome following mass spectrometry analysis as well as expression of neuronal FceR1a.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, inhibition of mGluRs, known to regulate histamine (34), abolished the anti-PrP antibody toxic effects (28). Taken together and in addition to the allergenic-related proteins associated with ICSM35 treatment reported by Tayebi and colleagues (21), this provides sufficient evidence to investigate the allergenic pathways potentially induced by treatment with anti-PrP antibodies which we refer to as "IgG-Mediated Neuronal Hypersensitivity". To that end, we treated mouse primary neurons (MPN), mouse neuroblastoma (N2a) and microglia (N11) cell lines with anti-PrP antibodies then assessed the neuronal allergenic proteome following mass spectrometry analysis as well as expression of neuronal FceR1a.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, experimental treatment with anti-PrP antibodies directed against PrP C led to neuronal apoptosis based on microscopic assessments (23,24,26). Upon further analysis, some of these studies also revealed that anti-PrP antibodies induced activation of allergenic-related proteins identified by the AllerGAtlas database (21,27,28). We therefore sought molecular confirmation of a neuronal type 2-like hypersensitivity process associated with anti-PrP antibody treatment of neurons and microglia in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inhibition of mGluRs, known to regulate histamine [34], abolished the anti-PrP antibody toxic effects [28]. Taken together and in addition to the allergenic-related proteins associated with ICSM35 treatment reported by Tayebi and colleagues [21], this provides su cient evidence to investigate the allergenic pathways potentially induced by treatment with anti-PrP antibodies which we refer to as "IgG-Mediated Neuronal Allergenic Toxicity".…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, experimental treatment with anti-PrP antibodies directed against PrP C led to neuronal apoptosis based on non-molecular microscopic assessments [23,24,26]. Upon further analysis, some of these studies also revealed that anti-PrP antibodies induced activation of allergenic-related proteins identi ed by the AllerGAtlas database [21,27,28]. We therefore sought molecular con rmation of a neuronal hypersensitivity/allergenic process associated with anti-PrP antibody treatment of neuroblastoma and microglia.…”
Section: Discussionmentioning
confidence: 99%